2008
DOI: 10.1007/s00264-008-0589-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of a dual-articulation acetabular cup system to prevent dislocation after primary total hip arthroplasty: analysis of 384 cases at a mean follow-up of 15 years

Abstract: The concept of a dual articulation acetabular cup was developed by Prof. Bousquet in 1974. This concept has been shown to provide high stability after revision and primary total hip arthroplasty. The aim of our study was to evaluate the incidence of prosthetic instability in a consecutive homogeneous series of 384 primary dual mobility cups. Incidence of instability and implant survival were evaluated. Mean follow-up was 15.3 years (range, 12-20). There was no early or late instability. On the acetabular side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
140
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(155 citation statements)
references
References 25 publications
8
140
0
7
Order By: Relevance
“…Dual-mobility articulations may help decrease instability after THA [3,5,6,8,10,11,13,15,16,20,24,26]. This is likely the result of the increased effective size of the femoral head as well as the expanded impingement-free ROM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dual-mobility articulations may help decrease instability after THA [3,5,6,8,10,11,13,15,16,20,24,26]. This is likely the result of the increased effective size of the femoral head as well as the expanded impingement-free ROM.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have also illustrated good aseptic survivorship and lower dislocation proportion with the use of dual-mobility articulations in primary THAs (Table 2). In an analysis of 384 dual-mobility hips, Philippot et al [24] observed a 4% dislocation proportion and cup survivorship of 97% at a minimum followup of 12 years. Similarly, Farizon et al [13] conducted a study examining 135 cementless dual-mobility hips and found a 0.7% dislocation proportion at a minimum followup of 10 years with 95% implant survivorship at 12 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this early period, a number of cemented and cementless designs have emerged in Europe, and some have been recently Food and Drug Administration-approved. Several studies have assessed the outcome of such devices in the prevention of dislocation in both primary and revision THAs [3,14,22,28,29,[37][38][39][40] and reported very low dislocation rates. Only two studies have assessed a dual mobility socket in the treatment of recurrent dislocation [21,30].…”
Section: Introductionmentioning
confidence: 99%